PENGUASAAN PESERTA DIDIK KELAS IX TERHADAP LAGU NASIONAL DI SMP NEGERI 10 PONTIANAK - Adril Tarrega Riadh; Nurmila Sari Djau; Yudhistira Oscar Olendo (Universitas Tanjungpura, 2023)
National songs play a crucial role in shaping Indonesia's national identity. At SMP Negeri 10 Pontianak, a noticeable number of students showed limited mastery of these songs. This school, established since 1979 and led by Ibu Rozani Nofelinda, S.Pd, M.Pd, functions with various curricula for different grades. The study utilized qualitative methods, such as observations and interviews. The findings highlighted that many students lacked adequate mastery of national songs. Factors impacting their proficiency include personal interest, motivation, teaching techniques, and external environment. The institution's vision emphasizes excellence, discipline, environmental mindfulness, faith, and devotion. Despite the national songs' curriculum not being mandatory, it was introduced to bolster students' nationalism, especially considering the decline in this practice during the two-year remote learning due to the pandemic. The results underscore that only a portion of the students excels in these national songs, indicating a pressing need for improved methods to foster and sustain national pride through mastery of these songs.